Simultaneous laser obliteration of recurrent veins and Baker’s cyst: indications, technique, results of treatment - A. I. Chernookov; M. R. Kuznetsov; N. Yu. Korobova; S. I. Kandyba; A. A. Atayan; A. A. Ramazanov; E. N. Belykh; A. M. Nikolaev; A. Z. Pshmakhova (Амбулаторная хирургия)
Introduction. The wide prevalence of varicose veins of the lower extremities and relapses of this disease causes a frequent combination of this pathology with other surgical and traumatological diseases. The expediency of using simultaneous operations is manifested in their obvious economic advantages.Objective. To substantiate the expediency and effectiveness of simultaneous laser thermal obliteration of recurrent veins of the lower extremities and Baker’s cyst.Materials and methods. 9 patients with recurrent varicose veins and Baker’s cyst were operated on. Of these, there were 7 (77.8%) women and 2 (22.2%) men, the average age was 52.8 ± 0.2 years. The average duration of the incidence of varicose veins was 14.1 ± 0.3 years, Baker’s cyst – 3.5 ± 0.1 years. As planned, patients underwent simultaneous laser endovenous coagulation of recurrent veins and intracavitary thermal obliteration of Baker’s cyst.Results. There were no complications, the duration of operations was 40.3 ± 0.4 minutes. The intensity of the pain syndrome in 6–8 hours after surgery was 4.1 ± 0.2 points. On the 10th day, no pain was observed in any patient. The duration of pain was 7.8 ± 0.4 days. Long-term results were studied 12–16 months after completion of treatment in 9 (100%) patients. Recurrent varicose veins were not detected. In 8 (88.9%) patients, complete obliteration of Baker’s cyst was established.Conclusions. Reliable obliteration of Baker’s cyst and recurrent varicose veins, 100% technical success, disappearance of clinical symptoms of this pathology, absence of relapses of both diseases in 8 (88.9%) patients after 12-16 months indicates high efficiency and indisputable prospects of such an approach to the treatment of this category of patients. However, the study is based on a small number of observations, so further accumulation of experience is required to generalize the results of the study.